Care leaver needs and accessibility: Findings from the first large‐scale project in Switzerland. Issue 1 (6th August 2020) - Jarczok, Marion; Knecht Krüger, Beatrice; Mitrovic, Tanja; Gérard, Gomera; Jud, Andreas
Abstract: Leaving out‐of‐home care is a challenging situation not only for young people leaving care but also for the child welfare system. However, systematic and multiorganizational transitional programmes are often lacking. This study investigated Switzerland's first large‐scale care leaver programme and analysed associations between care leavers' needs and contactability in a sample of 459 care leavers. A first track compared the characteristics of successfully contacted care leavers and of not contactable care leavers ('dropouts'). The second track analysed the association between need for support and self‐rated or proxy‐rated quality of life in the subsample of 235 successfully contacted care leavers. Odds for indicators of lower educational attainment were substantially increased for dropouts. Additionally, self‐reported need for support was significantly associated with lower self‐ratings of quality of life in seven areas. Care leavers who accepted the programme's offer of coaching rated their quality of life lower than participants who reported no need for support and participants who reported a need for support but turned down coaching. For successfully contacted care leavers, the programme gave access to coaching sessions to the young people the most in need. However, dropouts appeared more vulnerable and might therefore benefit even more from aftercare support.